The effect of selective serotonin and norepinephrine reuptake inhibitors on clinical outcome of COVID‐19 patients: A systematic review and meta‐analysis - Dena Firouzabadi; Fatemeh Kheshti; Saeed Abdollahifard; Erfan Taherifard; Mohammad Reza Kheshti (Health Science Reports, 2022)
Abstract Background and Aim Due to the high social and economic burden and also mortality and morbidity caused by coronavirus disease 2019 (COVID‐19) in the past few years, researchers have aimed at finding solutions to suppressing the severity of infection. Recently, selective serotonin and serotonin‐norepinephrine reuptake inhibitors (SSRI/SNRI) have been investigated as an adjuvant treatment for COVID‐19. The aim of the current study was to investigate the impact of SSRI/SNRIs on outcomes of COVID‐19 patients. Methods In this systematic review and meta‐analysis, a comprehensive search strategy consisting of relevant words was performed by two researchers in PubMed, Scopus and EMBASE libraries. Studies reporting the effect of SSRI and/or SNRI use in COVID‐19 patients' outcome were included. Hospitalization, mortality, hospitalization event, and length of hospital stay were considered as main outcomes of this study. Analysis was carried out using Comprehensive Meta‐Analysis (CMA‐version 2) and final data were reported as odds ratio (OR) and 95% confidence interval (CI). Results Our search led to the final selection of 9 articles including 15,287 patients. The effect of fluvoxamine, fluoxetine, and the overall effect of SSRI/SNRI use on mortality of COVID‐19 patients were investigated in 3, 2, and 7 articles, respectively. The results of our analyses showed that these medications could significantly decrease mortality of COVID‐19 patients (OR and 95% [CI]: 0.595 [0.467–0.758], 0.620 [0.469–0.821], and 0.596 [0.437–0.813]). The effect of SSRI/SNRIs on hospitalization events of COVID‐19 patients was not significant (OR: 0.240% and 95% CI: 0.041–1.4). Also, length of hospital stay was longer in patients who administrated SSRIs. Conclusion According to this study's results, SSRI/SNRIs may be effective in reducing mortality of COVID‐19 patients, suggesting the superiority of fluvoxamine to fluoxetine. The safety profile and affordable cost of SSRI/SNRIs for a short‐term use may be other reasons to propose them as beneficial medications in preventing mortality in COVID‐19.